AB0112 Pathogenetic mechanisms in early rheumatoid arthritis: possible correlation between th17 and treg cells and gut microbiota structure: a pilot study. (12th June 2018) - Guzzo, M.P.; Lucchino, B.; Bonfiglio, G.; Barbati, C.; Vomero, M.; Neroni, B.; Gioia, C.; Gagliardi, A.; Alessandri, C.; Valesini, G.; Schippa, S.; Di Franco, M.
Abstract : Background: In Rheumatoid Arthritis (RA) pathogenesis T helper17 (Th17) and T regulatory cells (Treg) are largely represented. 1 Recent studies highlighted the role of intestinal mucosa environment in modulation of T cells function. The composition of gut microbiota influences the Th17/Treg cells balance and the host immune response, 2 so the exposure to deranged intestinal microbiota may be crucial in RA. Objectives: The aim of the study was to compare Th17 and Treg cells and gut microbiota composition in patients with early RA (ERA) and in a control group (CG) at baseline and after treatment. Methods: Currently, 10 ERA patients and 10 subjects belonging to the CG have been enrolled. All ERA patients were evaluated before (T0) and after 3 months (T1) of treatment with methotrexate (MTX) and glucocorticosteroids (GCS). Blood and faecal samples were collected. After PBMC isolation, staining with coniugated mAbs targeting specific surface and intracellular antigens (CD4 and CD25, IL-17 and FoxP3 respectively) have been used in order to distinguish Th17 and Treg cells. The composition of the faecal microbiota has been analysed by Next Generation Sequences on Illumina MiSeq platform, through 16S rDNA V3-V4 targeted sequencing. Results: At T0, the percentage of Th17 cells was higher in patients than in the CG (p<0.0001) while Treg cells were higher in the CG (p=0.013). At T1, the total number of CD4 +and Th17 cells was decreased (p=0.007, p=0.027) while the frequency of Treg cells increased (p=0.028). A normalisation of Treg cells, with frequencies comparable to CG, was present after treatment. Regarding gut microbiota, at phylum level no difference between patients at T0 and the CG were present but we observed a tendency to decrease in the frequency of Actinobacteria after therapy. Furthermore, the relative abundance of Actinobacteria correlated positively with the circulating levels of Th17 (p=0, 012, r=0, 59) and with the Th17/Treg at T0 (p=0, 010, r=0, 6), while Nitrospirae correlated positively with Treg (p=0, 028, r=0, 68) at T1. A significant increase of the relative abundance in the Lachnospiraceae family in patients at T1 compared with T0 (p=0, 042) and CG (p=0, 043) were noticed. Conclusions: Our results highlight the presence of an imbalance between Th17 and Treg cells in patients with ERA. In agreement with literature, 3 MTX and GCS influence on Th17 decreasing and Treg cells increasing in patients with ERA, so we can hypothesise that part of the clinical response is own to the improvement in T cells balance. Previous data 4 reported that Actinobacteria are strongly correlated with the production of IL-17 and a reduction of Nitrospirae has been associated to increased inflammatory responses and to gut permeability in mice. 5 Lachnospiraceae family play an important role in the maintenance of intestinal homeostasis. 6 The correlation between gut microbiota composition and Th17/Treg axis observed in our patients may suggest the involvement of some bacteria family in Th17/Treg cells balance in the lamina propria of RA patients treated with MTX, even in the early phases of the disease. References: [1] Alunno, et al. 2015. [2] Omenetti, Pizarro. 2015. [3] Szalay, et al. 2013. [4] Chen, et al.2016. [5] Serino, et al. 2012. [6] Wu, et al. 2016. Disclosure of Interest: None declared